2022
DOI: 10.1111/nhs.12934
|View full text |Cite
|
Sign up to set email alerts
|

Impact of role conflicts and self‐efficacy on academic performance of graduate‐entry healthcare students: A lagged study

Abstract: Graduate entry healthcare students experience many challenges during their academic journey. The impact of these challenges needs to be considered to support students through their training and education. In this study, we examined the impact of experiencing these role conflicts (at the outset of the academic year), for example, family and caring responsibilities, activities with family/friends, and daily tasks/chores, on the academic performance (at the end of the academic year) of graduate‐entry healthcare s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The second-year nursing postgraduates in the present study reported receiving families support, which was motivated by love, the power of kinship, and the presence of family expectations for the postgraduates that were essentially aligned with their goals. As a result, participants stated that their family duties and student roles were well-balanced, which is beneficial to self-efficacy improvement [ 26 ] (subtheme “family support” under “extrinsic sources of research self-efficacy”). Family support is also a concern for first-year postgraduate students, as they are concerned about the financial burden of enrolling in school, which can be somewhat alleviated with the support of their families [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second-year nursing postgraduates in the present study reported receiving families support, which was motivated by love, the power of kinship, and the presence of family expectations for the postgraduates that were essentially aligned with their goals. As a result, participants stated that their family duties and student roles were well-balanced, which is beneficial to self-efficacy improvement [ 26 ] (subtheme “family support” under “extrinsic sources of research self-efficacy”). Family support is also a concern for first-year postgraduate students, as they are concerned about the financial burden of enrolling in school, which can be somewhat alleviated with the support of their families [ 27 ].…”
Section: Discussionmentioning
confidence: 99%